Mechanism Investigation of Air-side Fouling on Micro-channel Heat Exchanger for Household Refrigerator - Liu Jinwei; Jiang Fuzheng; He Liu; Ten Shizheng; Chen Jiangping (Zhileng xuebao)
The air-side pressure drop of micro-channel heat exchanger (MHE) is increased and the heat exchange performance is attenuated when the MHE is covered with dust particles. In this study, a visual experimental rig was set up to investigate the effect of air velocity, type of dust, relative humidity and whether the MHE is charged or not on dust accumulation. The experimental results indicate that dust particles were mostly deposited on the windward side of the slit fins and at the front part of the tubes at an air velocity of 1 m/s. The dust extended to the trailing edge of the fin at higher wind speed. When only particle dust was present, dust could hardly accumulate. However, as the fiber content increased, the particle-deposition process accelerated. Under the conditions of 100% Particle, 95% Particle + 5% fiber, and 92% Particle + 5% fiber + 3% long fiber, the air-side pressure drop were increased by 8.8%, 451.4%, and 524.9%, respectively. Under the conditions of 95% Particle + 5% fiber and 92% Particle + 5% fiber + 3% long fiber, the air volume were decreased by 31.6% and 48.7%. When the air relative humility was 45% and 65%, the air-side pressure drop were increased by 451.4% and 385.6%, and the the air volume were decreased by 31.7% and 26.4%. When the MHE was not charged or was charged by an alternating current at 3 V, the air-side pressure drop were increased by 385.6% and 278.3%, and the air volume were decreased by 26.4% and 18.4%, respectively.